Coherence analysis of the calcium activity of putative astrocytic and neuronal cells on the L5 ventral horn and neural output in activated lumbar CPG networks. (6th February 2022) - Yazawa, Itaru; Okazaki, Shuntaro; Yokota, Shigefumi; Takeda, Kotaro; Fukushi, Isato; Yoshizawa, Masashi; Onimaru, Hiroshi; Okada, Yasumasa
Highlights: Coherence analysis of the calcium activity of L5 ventral cells and neural output in fictive locomotion. Calcium activity of astrocytes and neurons synchronized with locomotor-like activity in a certain frequency range. These cells might be active with certain time lags to maintain synaptic function and metabolism in activated lumbar CPG networks. Abstract: Astrocytes are thought to play a crucial role in providing structure to the spinal cord and maintaining efficient synaptic function and metabolism because their fine processes envelop the synapses of neurons and form many neuronal networks within the central nervous system (CNS). To investigate whether putative astrocytes and putative neurons distributed on the ventral horn play a role in the modulation of lumbar locomotor central pattern generator (CPG) networks, we used extracellular recording and optical imaging techniques and recorded the neural output from the left L5 ventral root and the calcium activity of putative astrocytes and neurons in the L5 ventral horn at the same time when activating an isolated L1–L5 spinal cord preparation from rats aged 0–2 days. Optical measurements detected cells that showed a fluorescence intensity change under all experimental conditions, namely, (1) 5-HT + NMDA, (2) TTX, and (3) TTX + Low K + . These cells were semiautomatically identified using an in-house MATLAB-based program, as putative astrocytes and neurons according to the cell classification, i.e., increased or decreased fluorescence intensity change (ΔF/F0), and subjective judgment based on their soma size. Coherence and its phase were calculated according to the calcium activity of the putative astrocytes and putative neurons, and neural output was calculated during fictive locomotion with in-house MATLAB-based programs. We found that the number of putative astrocytes activated by applying low K + tends not to differ from that activated by applying the protease-activated receptor 1 (PAR1) selective agonist TFLLR-NH2 (TFLLR). Moreover, the calcium activity of several putative astrocytes and neurons synchronized with locomotor-like activity at a frequency range below 0.5 Hz and the time lag between peaks of cellular calcium activity and locomotor-like activity ranged from −1000 to + 1000 ms. These findings presumably indicates that these putative astrocytes and neurons in the left L5 ventral horn require −1000 to + 1000 ms to communicate with lumbar CPG networks and maintain efficient synaptic function and metabolism in activated lumbar CPG networks. This finding suggests the possibility that putative astrocytic and neuronal cells in the L5 ventral horn contribute to generating the rhythms and patterns of locomotor-like activity by activated CPG networks in the first to fifth lumbar spinal cord.